2019
DOI: 10.1002/wat2.1392
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater governance: Addressing core concepts and challenges

Abstract: With decreasing aquifer levels, increasing groundwater pollution, inequitable access, and generally poor management outcomes, better groundwater governance has been put forward as a recipe to address these challenges worldwide. Existing recommendations focus on improved legal frameworks, monitoring and control of access and abstraction through permits or formal rights. In addition, decentralized water management, enforcement of regulations, and supply‐side technological solutions are seen as cornerstone compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Water markets only exist within institutions and structures that allow and govern the transfer of water, and without strong institutions, market failure will occur and inequality issues will exist Wheeler and Garrick 2020). Hence, we agree with Closas and Villholth (2020) that strong groundwater governance studies must appropriately combine biophysical principles with sociopolitical realities to understand how and why extraction and management happen. Given the interdependence and substitutability that has been identified between different water sources, we suggest the many improvements in water governance that are needed in the MDB (and indeed around the world in many areas) include: (i) greater use of satellite and thermal imaging and measurement of all types of water extractions and how their extraction is changing over time; (ii) developing strong regional water resource plans to cover all types of water sources; (iii) increased metering, monitoring and enforcement; (iv) improved water hydrology and connectivity scientific knowledge; and (v) improved water trade products, appropriately designed and adaptable to account for changing human behaviour and other unintended consequences.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Water markets only exist within institutions and structures that allow and govern the transfer of water, and without strong institutions, market failure will occur and inequality issues will exist Wheeler and Garrick 2020). Hence, we agree with Closas and Villholth (2020) that strong groundwater governance studies must appropriately combine biophysical principles with sociopolitical realities to understand how and why extraction and management happen. Given the interdependence and substitutability that has been identified between different water sources, we suggest the many improvements in water governance that are needed in the MDB (and indeed around the world in many areas) include: (i) greater use of satellite and thermal imaging and measurement of all types of water extractions and how their extraction is changing over time; (ii) developing strong regional water resource plans to cover all types of water sources; (iii) increased metering, monitoring and enforcement; (iv) improved water hydrology and connectivity scientific knowledge; and (v) improved water trade products, appropriately designed and adaptable to account for changing human behaviour and other unintended consequences.…”
Section: Discussionmentioning
confidence: 71%
“…Poor understanding of the relationship between surface and groundwater resources and imperfect knowledge about drivers of irrigator behaviour can lead to ineffective water management policies (Zhang 2007;Famiglietti et al 2011;Kuwayama and Brozovi c 2013), leading to a call for the need for increased groundwater governance principles (e.g. Closas and Villholth 2020). Indeed, although there has been increasing emphasis on decentralization of natural resource management-with water markets increasingly encouraged for both surface and groundwater-many have also written that, for markets to be truly effective, there are many critical institutional and hydrological fundamentals to avoid market failure (Grafton et al 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars anticipated that the economics of supply and demand would drive an evolutionary transition from development to management as groundwater becomes scarce and those who retain access to it build regulatory institutions to ensure their continued control over the resource (Shah et al, 2003, cited in Hoogesteger, 2018, p. 554). All agree, however, that for the well‐being of all involved the “anarchy” (Shah, 2009) of groundwater development and the depletion it has engendered must give way to management (Kemper, 2007), or in more recent parlance, to governance (Closas & Villholth, 2020; Doornbos, 2003; Faysse & Petit, 2012; Zwarteveen et al, 2017).…”
Section: The Modern Development Of Groundwatermentioning
confidence: 99%
“…In the Middle East and North Africa region, experiences have shown that seeking government efficiency or accountability has not led to addressing equity, despite it seeming like a sensible approach. It is argued that policy instruments can only succeed if power dynamics consisting of influential actors and vested interests are taken into account (Closas & Villholth, 2020 ).…”
Section: International Environmental Agreements Of Water: Lessons Learntmentioning
confidence: 99%